2017
DOI: 10.1016/j.exger.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites related to renal function, immune activation, and carbamylation are associated with muscle composition in older adults

Abstract: Reduced skeletal muscle density in older adults is associated with insulin resistance, decreased physical function, and an increased all-cause mortality risk. To elucidate mechanisms that may underlie the maintenance of skeletal muscle density, we conducted a secondary analysis of previously published muscle composition and serum metabolomic data in 73 older adults (average age, 78y). Multivariable-adjusted linear regression was used to examine associations between 321 metabolites with muscle composition, defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 100 publications
1
16
0
Order By: Relevance
“…Statistical significance for between-group differences in taxonomy or functions was set at a p-value ≤ 0.05 and the false discovery rate at (FDR) ≤ 0.30. A FDR of 0.30 indicates that the result is likely to be valid 7 out of 10 times, which we suggest is reasonable in the setting of exploratory discovery (Lustgarten and Fielding, 2017).…”
Section: Methodsmentioning
confidence: 71%
“…Statistical significance for between-group differences in taxonomy or functions was set at a p-value ≤ 0.05 and the false discovery rate at (FDR) ≤ 0.30. A FDR of 0.30 indicates that the result is likely to be valid 7 out of 10 times, which we suggest is reasonable in the setting of exploratory discovery (Lustgarten and Fielding, 2017).…”
Section: Methodsmentioning
confidence: 71%
“…In a previous association study, higher levels of indole-3-lactate were found to be cross-sectionally associated with lower eGFR 16 . In an elderly population, indole-3-lactate was found to be associated not only with muscle composition but also with the renal function markers serum creatinine and blood urea nitrogen 78 . Quite recently, a study group reported that increased levels of indole-3-lactate were found to be associated with lower eGFR in a cohort of patients with ADPKD 79 .…”
Section: Discussionmentioning
confidence: 96%
“…One theory on the relation between kidney function and physical performance is that this accumulation of small molecules has a detrimental effect on other systems in the body [ 40 ], including those that govern physical performance – that declines in kidney function lead to declines in physical performance through serum metabolites. In support of this theory, two recent papers posit a relation between declines in kidney function and sarcopenia through serum metabolites [ 41 , 42 ]; however, the extent to which these findings apply to other physical performance measures is unclear. An alternative theory is that declines in kidney function and declines in physical performance are both governed by a common ‘accelerated aging’ phenotype [ 38 ], and that identified common metabolites may be markers of accelerated aging.…”
Section: Discussionmentioning
confidence: 99%